Extraction and antibacterial activity of nahar (Mesua ferrea) seed kernels’ oil - Adewale, Ahmed Idris; Mirghani, Mohamed Elwathig Saeed; Muyibi, Suleyman Aremu; Daoud, Jamal Ibrahim; Mikail, Maryam Abimbola (African City of Technology (ACT), 2011)
There is a growing need to explore more sustainable and alternative sources of oil as a result of the increasing demands for oils both for human consumption and other industrial applications. The aims of this work were thus; to determine the effect extraction temperature, time and solvent type on oil yield from Nahar (Mesua ferrea L.) seed kernels (NSK) and also to evaluate the antibacterial activity of the oil. The NSK oil extraction was carried out using soxhlet apparatus with n-hexane, ethanol, methanol, petroleum ether and chloroform, while the antibacterial activity was evaluated using disc diffusion and broth dilution methods. Chloroform gave the highest oil yield in all the experiments, while the yields of n- hexane, petroleum ether and ethanol were close. The crude oil yields obtained from the seed kernels for all the solvents, except methanol, at extraction time of 6hours and above, ranged from 70 - 84% of the seed kernel on dry weight basis. Chloroform gave the highest oil yield in all the experiments, while the oil yields of n- hexane, petroleum ether and ethanol were close. The antimicrobial assay of the crude oil extracts showed remarkable inhibitions against all the tested bacteria (Escherichia coli, Pseudomonas aeruginosa, Bacillus subtilis and Staphylococcus aureus). The minimum inhibitory concentration (MIC) of the oil for all the tested organisms ranged from 240-980μg/ml, while the minimum bactericidal concentration MBC) was 2mg/ml.